PERAN MAHASISWA KKM SEBAGAI AGEN PEMBELAJARAN DALAM PROGRAM BIMBINGAN BELAJAR UNTUK SISWA SEKOLAH DASAR - Siti Musayaroh (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2022)
As educated people, students should have an impact on the surrounding community. Student Work Lecture or Kuliah Kerja Mahasiswa (KKM) Program is one of the compulsory subjects taken by final third-year students and a course that allows students to have an impact on society. Often the KKM program targets the education sector through tutoring programs for elementary school students. This article aims to determine the role of Untirta Group 17 Thematic KKM students as learning agents in the tutoring program for elementary school students. A total of 10 elementary school students who participated in the program have filled out a questionnaire with 14 questions covering the four roles of learning agents, namely facilitator, motivator, motivator, and inspiration. The data was then retrieved using SPSS. The results show that students can act as facilitators and inspirers well. On the other hand, students need to increase their role as motivators when they become agents of learning in tutoring programs. The success of students being agents of learning can make students feel happy and comfortable when participating in the learning process.